Penerapan Protokol Kesehatan pada Masa “New Normal” di Terminal Tipe A Simbuang Kabupaten Mamuju - Agus Erwin Ashari; Haeranah Ahmad; Fahrul Islam (Politeknik Kesehatan Kemenkes Mamuju, 2022)
According to data from the COVID-19 Acceleration Task Force on June 13, 2020, there was an increase in positive cases of COVID-19 by 1,014 people, which led to a total of 37,420 cases. Bus stations as a land transportation entrance route, is something that allows it to be the entrance of the corona virus from various regions, especially during the